Model Komunikasi Manajemen Konflik Perkawinan Campuran (Studi Kasus pada Pasangan Suami Istri Berbeda Kewarganegaraan) - Luthfie Yanuar Werdyanto; Mohammad Kevin (PERSPEKTIF, 2020)
This research was motivated by the phenomenon that is currently occuring in todays Indonesian society that is marriage across the nation. The purpose of this study were: 1) To understand the conflicts that occur within mixed marriage. 2) And to know how to manage conflict from various problems that arise. The employedapproach is qualitative case study. The main subjects are two married couples of different nationalities as well as supporting informants that consists of two Household Assistants marriage couples with different citizenship. The results of the research note that each pair of different citizenship has a communication model that can be used to manage conflict that is arising. When there is a conflict they will identify each other's problems, then they will give each other solutions to solve the problem, then they will make a commitment to the conflict so that it does not happen again. They already feel a very complicated conflict to resolve, but they can still continue their marriage by putting aside such complicated matters.